ADM for solving linear second-order fredholm integro- differential equation - Karim, Mohd F.; Mohamad, Mahathir; Rusiman, Mohd Saifullah; Che-Him, Norziha; Roslan, Rozaini; Khalid, Kamil (2018)
In this paper, we apply Adomian Decomposition Method (ADM) as numerically analyse linear second-order Fredholm Integro-differential Equations. The approximate solutions of the problems are calculated by Maple package. Some numerical examples have been considered to illustrate the ADM for solving this equation. The results are compared with the existing exact solution. Thus, the Adomian decomposition method can be the best alternative method for solving linear second-order Fredholm Integro-Differential equation. It converges to the exact solution quickly and in the same time reduces computational work for solving the equation. The result obtained by ADM shows the ability and efficiency for solving these equations.